Evaluation of Babesia gibsoni GPI-anchored Protein 47 (BgGPI47-WH) as a Potential Diagnostic Antigen by Enzyme-Linked Immunosorbent Assay - Zhan, Xueyan; Yu, Long; An, Xiaomeng; Liu, Qin; Li, Muxiao; Nie, Zheng; Zhao, Yangnan; Wang, Sen; Ao, Yangsiqi; Tian, Yu; He, Lan; Zhao, Junlong (Frontiers in Veterinary Science, 2019)
Babesia gibsoni is one of the important pathogens causing severe incurable canine babesiosis. In this case, a sensitive, specific, and highly automated diagnostic method is required in clinic. Surface proteins are ideal candidates for diagnostic targets because these proteins are the primary targets for host immune responses during host-parasite interactions. Glycosylphosphatidylinositol (GPI) -anchored proteins which are abundant on the surface of parasites play an important role for parasite diagnosis. In this study, a GPI-anchored protein named BgGPI47-WH was obtained. Mouse anti-rBgGPI47-WH polyclonal antibody was produced by immunizing mice. Western blot analysis was used to identify the native form and immunogenicity of BgGPI47-WH. Then an ELISA method was established by using recombinant BgGPI47-WH protein to evaluate its potential as a diagnostic antigen. The results showed that the established method has a high specificity and could be used for early stage diagnostic. It can recognize antibodies at day six until day 101 from experimental infected dogs. In order to evaluate the established ELISA, 147 clinical samples were collected from animal hospital. The results showed that 17.0% (25/147) of samples were positive. Compared to the results of ELISA based on BgSA1, the overall proportion agreement is 86.39%.Our results indicated that BgGPI47-WH could be a reliable diagnositic antigen and this study provides a practical method for the early diagnosis of Babesia gibsoni.